Condom use likelihood within the context of PrEP and TasP among men who have sex with men in Florida: a short report. Issue 3 (4th March 2022) - Algarin, Angel B.; Shrader, Cho Hee; Hackworth, Benjamin T.; Ibanez, Gladys E.
ABSTRACT: Despite the development of targeted interventions for men who have sex with men, this population continues to comprise the majority of new HIV diagnoses. Though condoms are highly efficacious, some sexually active MSM use sero-sorting as a method of HIV prevention. This study aimed to characterize: (1) differences between partner sero-status and condom use likelihood, and (2) demographic, behavioral, and knowledge-related factors influencing condom use likelihood with varying sero-status partners. Using convenience sampling, 150 sexual and gender minority men completed a survey on PrEP and sexual behaviors. The majority of participants identified as racial/ethnic minorities (51.7%), having 4 years of college or more (52.0%), and being HIV-negative (not on PrEP) (68.8%). Our sample reported the lowest average condom use likelihood with a partner on PrEP (2.93 ± 1.39) and the highest average likelihood with an HIV-positive partner (unknown VL) (4.57 ± 0.98). Age, race/ethnicity, education, HIV-status, and HIV and PrEP knowledge were significantly associated with differences in condom use likelihood. Our findings elucidate the complexity of sero-sorting scenarios and decision-making processes in the context of biomedical HIV prevention. These results may provide insight for future condom use and sero-sorting interventions in the context of biomedical HIV prevention.